PENILAIAN PARTISIPATIF DALAM ANALISIS POTENSI AGROWISATA KECAMATAN TOMPOBULU KABUPATEN MAROS SULAWESI SELATAN - Iswoyo, Hari; Dariati, Tigin; Dermawan, Rahmansyah (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2018)
The main activity is a survey aimed to analyze the potential of agro-tourism in Tompobulu Sub-district of Maros Regency which is represented by two villages: Benteng Gajah and Pucak. The survey was performed by empowering students who are underdoing community service activities (KKN) in the area. They conducted survey through visual and participative observation. The method consisted of physical and non-physical analysis. Physical aspects include landscape character, natural potential, physical constraints, hazard (danger signal) and support of existing facilities and infrastructure. While non-physical aspects related with vegetation and the use of vegetation by the community and its social relevance. The result of observation and participative interaction of the students described in descriptive narrative shows that Pucak Village and Benteng Gajah Village have some type of landscape character which has potential to be developed as agro-tourism. Potential characters include: mountain/hills, rivers with waterfalls, natural forests as well as rice fields and farms. Each character has the same percentage of observations that is 14.56%. This value is the largest among the percentage of observations of other characters. The reason that these characters generally have potential is that they are all accessible (23.65%) have interesting views (22.20%) with good hydrological networks (20.12). The perceived obstacles include poor road physical condition (28.00%) and no electricity grid (28.00%). For certain characters (hills and rivers) surveyors are concerned about threats of endemic disruption of local factors (60.61%), flooding threat (21.21%) and landslide (18.18%). Vegetation is used by the general public for food and housing materials. Based on the result of this survey, it can be concluded that the District of Tompobulu especially in the village of Pucak and Benteng Gajah have some landscape character which have potential to be developed into agro-tourism, supporting Pucak Teaching Farm which has already been established. Keywords: Agro-tourism, potential analysis, landscape characters, Tompobulu, Maros